Comportamiento de los tipos de cambio internacional y doméstico durante la inestabilidad financiera - Palomino Selem, Carlos (2012)
In this paper we demonstrate that the performance of Peru´s financial exchange rate is determinated significantly for the performance of USD like conducting currency in the international financial market It is important to say that the policy of exchange rate policy in Perú into of a scheme Banco Central de Reserva del Perú’s (BCRP) has a constraint from the outside, indirectly of Federal Reserve Bank in United State of American. Our research concludes that the framework to learn the financial markets and particularly the currency markets is in the approach of assets portfolio, where investor make decisions looking for returns of these assets and their currencies. This characteristic has been deepen since financial crises in the 2008 and appears when the financial system experience liquidity risk. In this situation the USD be appreciated respect to rest of currencies.